2013
DOI: 10.1186/2052-4374-25-5
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Liver Function Tests to Mixed Exposure to Lead and Organic Solvents

Abstract: Objective: This study aims to compare liver function indices (aspartate aminotransferase [AST], alanine aminotransferase [ALT], and gamma glutamyl transferase [GGT]) among males who work with lead, organic solvents, or both lead and organic solvents, under the permissible exposure limit (PEL).Methods: A total of 593 (out of 2,218) male workers who agreed to share their personal health information for medical research were selected for this study. Those excluded were hepatitis B carriers, individuals exposed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 43 publications
4
22
1
Order By: Relevance
“…The elevated levels of these enzymes found in this study are consistent with the other published studies where increased liver enzymes have been reported for adult subjects who have been exposed to benzene or petroleum products and organic solvents [34][35][36][37][38]. Since benzene exposure causes dysfunction of hepatic tissues, it may lead to the liberation of increased levels of hepatic enzymes into the circulation.…”
Section: Discussionsupporting
confidence: 82%
“…The elevated levels of these enzymes found in this study are consistent with the other published studies where increased liver enzymes have been reported for adult subjects who have been exposed to benzene or petroleum products and organic solvents [34][35][36][37][38]. Since benzene exposure causes dysfunction of hepatic tissues, it may lead to the liberation of increased levels of hepatic enzymes into the circulation.…”
Section: Discussionsupporting
confidence: 82%
“…The results demonstrated that the serum levels of ALP, GGT, AST and ALT were found to be elevated in the benzene exposed rats compared to the untreated reference group. Several other investigators also reported elevated liver enzymes among subjects exposed to benzene or petroleum products and organic solvents (Uzma et al, 2008;Mohammadi et al, 2010;Chang et al, 2013;Mark et al, 2014). The increased serum levels of these enzymes could be due to the overproduction or release of enzymes from the liver cells in response to stimuli of hepatocellular injury or cell death (Mark et al, 2014).…”
Section: Discussion:-mentioning
confidence: 91%
“…This solvent may affect the central nervous system, liver, and kidneys. Recently, Chang et al 14) reported that exposure to both lead and organic solvents is dangerous, even if exposure to each of the individual components is within the respective permissible limit. In the present case, the patient developed symptoms during exposure to DCP and TCE and within 1 year of exposure to DCM.…”
Section: Discussionmentioning
confidence: 99%